A screen printed carbon electrode modified with carbon nanotubes and gold nanoparticles as a sensitive electrochemical sensor for determination of thiamphenicol residue in milk. Issue 5 (11th January 2018) - Muhammad, Aliyu; Hajian, Reza; Yusof, Nor Azah; Shams, Nafiseh; Abdullah, Jaafar; Woi, Pei Meng; Garmestani, Hamid
Abstract : The first portable electrochemical sensor was constructed for monitoring of thiamphenicol residue in fresh milk based on electro-oxidation of thiamphenicol on the surface of CNTs and AuNPs. Abstract : Antibiotic residues in milk are of great concern for health regulatory agencies, milk consumers, and dairy farmers due to their destructive effects, ranging from allergic reactions, antibiotic resistance and the ability to interfere with the production of fermented products ( i.e. cheese and yogurt). Therefore, a reliable, fast, and simple method needs to be developed to monitor antibiotic residues in milk samples before distribution to consumers. In this study, the first sensitive electrochemical sensor is presented for the determination of thiamphenicol (TAP), a broad-spectrum antibiotic in bovine milk. In the fabrication process, a screen printed electrode (SPE) was modified with gold nanoparticles (AuNPs) and carbon nanotubes (CNTs) using ethylenediamine (en) as a cross linker. Cyclic voltammetry studies showed an adsorptive control process for the electro-oxidation of TAP at −0.1 V on the modified electrode of SPE/CNT/en/AuNPs. Differential pulse voltammetry (DPV) was applied for the quantitative determination of TAP under optimized conditions (0.1 M citrate buffer, pH 6.0, accumulation potential −0.7 V, and accumulation time 150 s). A DPV study for TAP shows a wide linear calibration range of 0.1–30 μM with the detection limit of 0.003 μM. Furthermore, the developed sensor displays high sensitivity, reproducibility, repeatability, and good stability for the detection of TAP. The proposed sensor was successfully applied for the determination of spiked TAP in bovine milk with satisfactory results.